Potential – Current characteristics of lunar surface at average solar wind conditions. Issue 2 (15th July 2022) - Rakesh Chandran, S.B.; Veenas, C.L.; Asitha, L.R.; Parvathy, B.; Rakhimol, K.R.; Abraham, A.; Rajesh, S.R.; Sunitha, A.P.; Renuka, G.
Abstract: The plasma environment of the Moon is dominated by the solar wind- the most energetic particles from the Sun. In this paper, we present an analysis of Lunar Prospector Electron Reflectometer data from the selected time periods to predict the lunar surface electrostatic potential over the dayside and nightside with respect to the ambient plasma. Here average solar wind condition (when the electron energy is below 100 eV) data was used to predict the surface potential. We used probe theory to derive the potential values. On the dayside, the potential is 5 V and on the nightside, it reaches up to −82 V. The variations in electron temperature ( T e ) values show strong dependence in the night side potential values. The potential reaches a value of −82 V at T e  = 58 eV. Our calculated values agree well with the values measured by the Electron Reflectometer instrument aboard the Lunar Prospector spacecraft. We investigate the variation of the electric field over the two regions and located a transition region on the surface where the potential value is almost zero. This region is most suited for exploration activities, as the region is free from hazards caused by surface charging.